Mental health legislation in the Philippines: Philippine Mental Health Act. (August 2019) - Lally, John; Samaniego, Rene M.; Tully, John
Abstract : The first mental health act legislation in the history of the Philippines has been officially signed into law and was enacted as the Republic Act no. 11036 on 21 June 2018. It provides a rights-based mental health bill and a comprehensive framework for the implementation of optimal mental healthcare in the Philippines. We review the principles and provisions of the Mental Health Act of 2017 and the implications for mental healthcare in the Philippines.